Effectiveness and Risk Management Strategies on the Use of Chat GPT in the Field of Academic Education - Putri, Aqirino Rani; Wahyudi , Tri Nur (Lectura : Jurnal Pendidikan, 2025)
In this era of technological development, Chat GPT comes as an innovation that offers various benefits and challenges in education. It opens new opportunities for more interactive and personalized learning but also tests our readiness to manage its ethical and academic impacts. This study aims to understand how students cope with risks and use Chat GPT effectively. his research used a mixed method with a sequential exploratory approach. The object of this research was Universitas Muhammadiyah Surakarta, while the subject was Accounting Education Study Program students. Data collection techniques included observation, interviews, documentation (qualitative), and questionnaires (quantitative). The number of informants was 5 students (qualitative), and there were 105 respondents (quantitative). The results of this study indicated that the use of Chat GPT was 73.3% for completing coursework, 55.2% for looking for references and literature, 37.1% for making summaries, and 23.8% for translating languages. The risks of using Chat GPT were 65.7% excessive dependence, 61.9% reducing critical thinking skills, 40% high plagiarism, and 32.4% inaccurate and difficult-to-understand information. For strategies used to overcome the risks of using Chat GPT, 28.6% of respondents used Chat GPT answers only as references, 27.6% paraphrased in their own language, 24.8% double-checked answers with other sources, and 19% limited the use of Chat GPT. So, Chat GPT Chat is very effective in helping students complete academic assignments.